Percutaneous Grafting and Screw Fixation in Patients with Scaphoid Nonunion - Sener, Muhittin; Zengin, Eyup Cagatay; Saruhan, Sertac (Revista Brasileira de Ortopedia, 2021)
Objective The aim of the present study was to analyze the clinical and radiological results of patients with type-V cystic scaphoid nonunion who were treated with percutaneous grafting and screw.Methods A total of 11 patients were treated with a percutaneous bone graft with screw fixation. The criteria for inclusion in the study were a type-V scaphoid nonunion and age > 18 years old. Those with humpback deformity, arthritis, ligament damage determined on magnetic resonance imaging, or avascular necrosis (AVN) in the nonunion fragment were excluded from the study.Results The mean follow-up time was 36 months (range: 15–53 months). At the final follow-up examination, the mean visual analogue scale score was 1.06 (range: 0–2.3). Postoperatively, the mean extension was 61.6° (44–80°), flexion 66° (60–80°), radial deviation 12° (7–20°), and ulnar deviation 25° (20–34°). The mean grip strength of the operated hand was found to be 94%, compared with the healthy side. The results obtained in the Mayo Modified Wrist Score were poor in 2 patients, good in 2 and excellent in 7 (64%). With the exception of 2 patients, union was obtained radiologically in 9 patients, with a mean of 12.6 weeks (range, 8–16 weeks).Conclusion Percutaneous grafting and screw fixation cannot replace open surgery in cases with deformity, shortening, humpbacking, or in long term nonunions; however, it is a reliable and effective treatment method in selected cases, such as Slade & Dodds type-V cystic nonunion.
Keywords: scaphoid bone; fracture fixation, internal; bone grafting; bone screws